2002
DOI: 10.1103/physreve.65.056201
|View full text |Cite
|
Sign up to set email alerts
|

Markov models from data by simple nonlinear time series predictors in delay embedding spaces

Abstract: We analyze prediction schemes for stochastic time series data. We propose that under certain conditions, a scalar time series, obtained from a vector-valued Markov process can be modeled as a finite memory Markov process in the observable. The transition rules of the process are easily computed using simple nonlinear time series predictors originally proposed for deterministic chaotic signals. The optimal time lag entering the embedding procedure is shown to be significantly smaller than the deterministic case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 12 publications
4
116
0
Order By: Relevance
“…The dimension of the embedding was set using the Cao criterion [25], while the embedding delay time was set as the autocorrelation decay time. Other criteria to obtain embedding parameters, such as described in [19], provide similar results. Furthermore, each time series was time-delayed, so that they had maximal mutual information with the destination of the flow.…”
Section: Tests On Simulated and Experimental Datasupporting
confidence: 65%
See 1 more Smart Citation
“…The dimension of the embedding was set using the Cao criterion [25], while the embedding delay time was set as the autocorrelation decay time. Other criteria to obtain embedding parameters, such as described in [19], provide similar results. Furthermore, each time series was time-delayed, so that they had maximal mutual information with the destination of the flow.…”
Section: Tests On Simulated and Experimental Datasupporting
confidence: 65%
“…We consider three simultaneously measured time series generated from stochastic processes X, Y and Z, which can be approximated as stationary Markov processes [19] of finite order. The state space of X can then be reconstructed using the delay embedded vectors x(n) = (x(n), ..., x(n − d x + 1)) for n = 1, .…”
Section: Entropy Combinationsmentioning
confidence: 99%
“…For a chaotic deterministic system the delay should be of the order of the first minimum of the time delayed mutual information [22]. For a dynamical system of Langevin type the delay should be smaller than this, depending on the noise level [17]. We use the delay that minimizes the mean prediction error.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of tools have been developed for this case [16]. Recently, it has been shown that models originally proposed for deterministic chaotic systems also apply if the underlying dynamics is governed by a Markov process [17]. Let us outline first how phase space models are constructed for deterministic chaotic systems, and then we will show why these algorithms work for Markovian processes as well.…”
Section: Nonlinear Modelmentioning
confidence: 99%
“…Such processes are called hidden Markov processes (HMP) [25]. An HMP can also be understood as a Markov process with noisy observations, providing a nonlinear stochastic approach that is more appropriate for signals with noisy components [26].…”
Section: Hmm-based Entropy Measuresmentioning
confidence: 99%